2018
DOI: 10.21037/jovs.2018.05.17
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid robotic thoracic surgery for excision of large mediastinal masses

Abstract: Between April 2016 and October 2017, we retrospectively reviewed all patients undergoing excision of large mediastinal masses using a hybrid robotic thoracic approach at the Unit of Thoracic Surgery of Monaldi Hospital in Naples. The inclusion criteria for this approach were: evident unilateral predominance of the mass; absence of invasion to surrounding structures. Planned conversion to sternotomy was necessary in one patient for tenacious adhesions between the mediastinal goiter and the left innominate vein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Different surgical approaches can be utilized to manage mediastinal masses, including median sternotomy, thoracotomy, mediastinoscopy, video-assisted thoracoscopic surgery (VATS), and robotic-assisted thoracoscopic surgery (RATS). 10,11 To our knowledge, no previous study has shown a correlation between the presence of symptoms and a particular operative approach. The aim of this study is to further describe the prevalence and characteristics of symptoms from a mediastinal mass and to determine if the presence of symptoms has an effect on postoperative outcomes.…”
Section: Introductionmentioning
confidence: 90%
“…Different surgical approaches can be utilized to manage mediastinal masses, including median sternotomy, thoracotomy, mediastinoscopy, video-assisted thoracoscopic surgery (VATS), and robotic-assisted thoracoscopic surgery (RATS). 10,11 To our knowledge, no previous study has shown a correlation between the presence of symptoms and a particular operative approach. The aim of this study is to further describe the prevalence and characteristics of symptoms from a mediastinal mass and to determine if the presence of symptoms has an effect on postoperative outcomes.…”
Section: Introductionmentioning
confidence: 90%
“…A combination of robotic systems and AI is the future tool in the medical field. The complex structure of the mediastinum makes it easy to injure the spinal cord, cervical nerve roots, hilum of the lung, and unnamed vessels and nerve branches during the surgical approach, and renders fat removal during the surgical procedure difficult [61][62][63]. Completely depending on humans is not reliable enough.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…Ausgehend von den guten Ergebnissen der roboterassistierten Thymuschirurgie vor allem bei Myasthenia gravis [6,7] wurden zunehmend auch Mediastinaltumoren im vorderen und hinteren Mediastinum roboterassistiert minimalinvasiv entfernt [8,9]. Mit steigender operativer Expertise können heute erweiterte Resektionen bei größeren Tumoren mit hoher Sicherheit und geringem perioperativem Trauma durchgeführt werden, wobei Langzeitergebnisse noch abgewartet werden müssen [10].…”
Section: Introductionunclassified